Productivity costs of cardiovascular disease mortality across disease types and socioeconomic groups - Hannah Elizabeth Carter; Deborah Schofield; Rupendra Shrestha (Open Heart)
Background Cardiovascular disease (CVD) is the single largest contributor to global mortality. Premature mortality due to CVD results in a loss of productivity, with associated economic and policy implications that are often overlooked.Methods A human capital approach was adopted to project the long-term impacts of Australian CVD deaths in 2003 on labour force participation and the present value of lifetime income (PVLI) forgone. Impacts were modelled to the year 2030 and accounted for individual characteristics at the time of death including age, sex and socioeconomic status.Results Premature deaths due to CVD in 2003 accounted for 51 659 working years and $2.69 billion in PVLI forgone when modelled to 2030 (95% CI $2.63 billion to $2.75 billion). The labour force impacts were highest for individuals aged between 35 and 64 at the time of death, and male deaths accounted for 87% of the total PVLI loss. The most costly disease type was ischaemic heart disease, followed by stroke and inflammatory heart disease. Deaths occurring in individuals residing in the most socioeconomically disadvantaged areas at the time of death had a disproportionately large impact on the total PVLI loss.Conclusions This study quantifies the relative productivity costs of CVD mortality across a range of disease types and socioeconomic groups. The magnitude of these costs highlights the scope for investments in effective healthcare interventions to provide positive economic returns and may assist decision makers in allocating resources among competing priorities.